Variation in the size of eggs of Chubut Steamer Ducks (Tachyeres leucocephalus) - Svagelj, Walter Sergio (2012)
Although several studies have analysed spatial or temporal variation in the size of eggs in waterfowl (Anseriformes), no study has analysed variation throughout the breeding range of a species. Chubut Steamer Ducks (Tachyeres leucocephalus) are flightless marine waterfowl endemic to a small section of coastline in Patagonia, Argentina. We partitioned and analysed sources of variation in the size of 989 Chubut Steamer Duck eggs, from 175 clutches, obtained during the breeding seasons of 1998 and 2004-08 at 31 islands throughout the range of the species. In relation to other Anseriformes, we found a low level of variation (coefficient of variation=6.4%) at the species level. Most variation in the size of eggs were within clutches (59.0%) and among clutches (34.5%); variation between islands within geographical areas accounted for only 6.5% of variation, and there was no variation among geographical areas. Variation in size of eggs was not related to year, apparent clutch-size or latitude. The low variation at the species level and the lack of variation in size of eggs between geographical areas could be a consequence of the low genetic diversity and restricted distribution of the species. This study highlights the potential importance of variation in egg-size for understanding ecological processes linked to the natural history of avian spec © 2012 BirdLife Australia.ies.